2020
DOI: 10.1002/adfm.201910335
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex SERS Detection of Metabolic Alterations in Tumor Extracellular Media

Abstract: The composition and intercellular interactions of tumor cells in the tissues dictate the biochemical and metabolic properties of the tumor microenvironment. The metabolic rewiring has a profound impact on the properties of the microenvironment, to an extent that monitoring such perturbations could harbor diagnostic and therapeutic relevance. A growing interest in these phenomena has inspired the development of novel technologies with sufficient sensitivity and resolution to monitor metabolic alterations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 51 publications
1
92
0
Order By: Relevance
“…The lowest concentration that could be reliably distinguished using these scaffolds was 100 × 10 −9 m , which lies within the range of metabolite concentrations typically observed in biological environments, such as the tumor microenvironment. [ 36 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest concentration that could be reliably distinguished using these scaffolds was 100 × 10 −9 m , which lies within the range of metabolite concentrations typically observed in biological environments, such as the tumor microenvironment. [ 36 ]…”
Section: Resultsmentioning
confidence: 99%
“…The lowest concentration that could be reliably distinguished using these scaffolds was 100 nM, which lies within the range of metabolite concentrations typically observed in biological environments, such as the tumor microenvironment. [36] Although elasticity measurements (see above) indicated that the surface coating on AuNPs has a negligible effect on the rheological properties of HAMCA inks, the accessibility of the analyte molecules to the plasmonic gold NP surface is likely to hinder the SERS efficiency when NPs are stabilized with PEG. We therefore recorded 2D SERS maps for scaffolds containing AuNRs, AuNSs, AuNRs@PEG and AuNS@PEG.…”
Section: D and 3d Sers Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53] NP-induced differences in the cell metabolism cause changes in the composition of cells as well as the extracellular medium due to variations in the nature and quantity of the molecules uptaken by and released from the cells. [54] Although metabolomics is traditionally performed with mass spectroscopy, Raman spectroscopy, in particular surface enhanced Raman spectroscopy (SERS), has shown promise for the metabolic profiling of the cellular activity of bacterial cells and human cancer cells, [55][56][57][58][59][60] as well as for the detection of biomarkers in serum. [55,61,62] SERS is a vibrational spectroscopy that provides unique opportunities for signal amplification in aqueous media as water has low Raman cross-sections while the signal from Raman-active molecular vibrational modes in analytes can be enhanced by multiple orders of magnitude due to an electromagnetic enhancement effect in the vicinity of nanostructured noble metal surfaces.…”
mentioning
confidence: 99%
“…[54] Although metabolomics is traditionally performed with mass spectroscopy, Raman spectroscopy, in particular surface enhanced Raman spectroscopy (SERS), has shown promise for the metabolic profiling of the cellular activity of bacterial cells and human cancer cells, [55][56][57][58][59][60] as well as for the detection of biomarkers in serum. [55,61,62] SERS is a vibrational spectroscopy that provides unique opportunities for signal amplification in aqueous media as water has low Raman cross-sections while the signal from Raman-active molecular vibrational modes in analytes can be enhanced by multiple orders of magnitude due to an electromagnetic enhancement effect in the vicinity of nanostructured noble metal surfaces. [63][64][65][66][67] This amplification of molecule-specific vibrational information facilitates a sensitive detection and identification of metabolites rapidly without the need for elaborate sample preparation or enrichment.…”
mentioning
confidence: 99%